2019
DOI: 10.3390/app9183938
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation through Conductive Substrate to Enhance Osteo-Differentiation of Human Dental Pulp-Derived Stem Cells

Abstract: Human dental pulp-derived stem cells (hDPSCs) are promising cellular sources for bone healing. The acceleration of their differentiation should be beneficial to their clinical application. Therefore, a conductive polypyrrole (PPy)-made electrical stimulation (ES) device was fabricated to provide direct-current electric field (DCEF) treatment, and its effect on osteo-differentiation of hDPSCs was investigated in this study. To determine the optimal treating time, electrical field of 0.33 V/cm was applied to hDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…19,21,22 Recently, Cheng et al demonstrated that electrically conductive films increased osteogenic differentiation of human DPSCs. 23 Despite these recent findings, exactly how EStim influences dental tissuederived stem cells is poorly understood. In this study, we investigated the effects EStim has on osteo-/ odontogenic potential of DPSCs, with an eye toward its potential use in combination with TE approaches for improving outcomes in dental treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,21,22 Recently, Cheng et al demonstrated that electrically conductive films increased osteogenic differentiation of human DPSCs. 23 Despite these recent findings, exactly how EStim influences dental tissuederived stem cells is poorly understood. In this study, we investigated the effects EStim has on osteo-/ odontogenic potential of DPSCs, with an eye toward its potential use in combination with TE approaches for improving outcomes in dental treatments.…”
Section: Discussionmentioning
confidence: 99%
“…32 Lower electrical resistance on polypyrrole (PPy) films was found to correlate with higher levels of mineralization in DPSCs. 23 Oliveira, et al; BioResearch Open Access 2020, 9.1 http://online.liebertpub.com/doi/10.1089/biores.2020.0002…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro experiments that exposed cells and/or scaffolds to EStim, demonstrated its ability to influence cell functions associated with enhanced bone healing [7][8][9][10][11][12][13][14]. These experiments were conducted on a variety of different cell types; bone marrow-derived mesenchymal stem cells (BM-MSC), from human and animal origin [10,11,[15][16][17][18][19][20][21][22][23][24][25]; adipose-derived mesenchymal stem cells (AT-MSC) [11,20,[26][27][28][29][30], mouse osteoblast-like cells [31][32][33] and more recently, human dental pulp stem cells (DPSC) [34]. The above cell types are commonly studied for use in BTE applications.…”
Section: Estim's Effects On Cell Functionmentioning
confidence: 99%
“…Several works have been published in this Special Issue regarding the experimentation of the different techniques in BTE to enhance bone growth and regeneration processes. Cheng et al [6] applied an electrical stimulation on human dental pulp-derived stem cells to promote bone healing. The results presented in this work are promising, and reveal an enhancement in calcium deposition at different days of the tests.…”
Section: Contentsmentioning
confidence: 99%